Utredning av täckningsgrad vid alternativ placering av brandstationer i Luleå kommun : En GIS-analys av responstid - Nordberg, Johannes (2013)
The fire department in municipal of Luleå has at present time three fire stations, in Luleå, Gammelstad and Råneå, that serve 75 000 residents on a 2100 square kilometers large area. Large investments need to be done in a near future to either maintain the function of the station in the town center of Luleå or build a completely new one. At the same time the department faces new challenges since the municipality has developed an expansionell working basis, Vision Luleå 2050, with focus on population growth and expansion in the municipal. The fire department has therefore on behalf of the rescue committee, started a project that investigates possible solutions of locating new fire stations. This survey investigates the issue of optimal placement of new fire stations with consideration to drive time. Considering the present localization, the only station that definitely will remain on the same place is the one in Råneå. The purpose is to investigate how different solutions affect the response coverage and if it reaches at least as god capability as the present.Information on how the study should proceed was gathered and an important part of this is to learn from other fire departments. Also a few theses about the subject were studied and a report made by Sundbom (2009) concludes important factors for strategic localization of fire stations. The study also examines Swedish legislation that treats placement for fire stations, one of them is the fairly new Law of protection against accidents. At the moment there are no legislation that in detail control drive time and placement of fire stations. Therefore an old recommendation of response coverage persists to a large extent amongst fire departments.The most important factor in this study is response coverage to the residents in the municipal but also accidents together with risk and protection objects are taken into consideration to determine optimal location. The municipality action program of the fire department highlight three accidents with greater demands on a ...